Associations of spiders of the genus Peucetia (Oxyopidae) with plants bearing glandular hairs - Vasconcellos-Neto, Joao; Romero, Gustavo Q.; Santos, Adalberto J.; Dippenaar-Schoeman, Ansie S. (Blackwell Publishing, 2007)
Two common South American species of lynx spiders, Peucetia rubrolineata and P. flava (Oxyopidae), were surveyed on three localities in southeastern Brazil to determine plant choice. Both species were found to be associated with plants bearing glandular trichomes. A literature review and complementary data show that ten Peucetia species are associated with up to 55 plant species bearing glandular trichomes in at least 20 distinct vegetation types (phytophysiognomies) in more than 36 localities in the Neotropical, Neartic, Afrotropical, and Paleartic regions. The main plant families used by the spiders were Solanaceae, Asteraceae, and Melastomataceae. The specialization of the Peucetia species for plants bearing glandular trichomes may have evolved because insects adhered to these sticky structures may be used as prey by the spiders.
Keywords: evolution; foraging; host plant specificity; lynx spider; Specific association